Integrative taxonomy approach to the study of parasitic ergasilids (Cyclopoida: Ergasilidae) of fishes from the Pardo River, Brazil with a redescription of Rhinergasilus piranhus Boeger and Thatcher, 1988 and a molecular phylogeny for Ergasilidae - Rodrigo Bravin Narciso; Nico J. Smit; Gilmar Perbiche-Neves; Reinaldo José da Silva (Parasitology)
Brazil has the richest biodiversity of Ergasilidae on Earth, with 76 species in 19 genera. However, several authors suggested that there is still great potential for discoveries, especially regarding genetic data that are still scarce for ergasilids from this region. To expand our knowledge of this taxon, we conducted an integrative study involving morphological (light and scanning electron microscopy) and molecular analyses of ergasilids from fishes sampled in the Pardo River, São Paulo State, Brazil. Two ergasilid species were found, Gamispatulus schizodontis and Rhinergasilus piranhus parasitizing the nostrils of 5 fish species (native and exotic): (i) R. piranhus from Astyanax lacustris; Cyphocharax modestus; Coptodon rendalli; Psalidodon bockmanni; and (ii) G. schizodontis from Serrasalmus maculatus. Additionally, we redescribed R. piranhus herein based on novelties and discrepancies found in the antennules, antennae, body segments and ornamentation of the swimming legs. Novel molecular data of ribosomal (18S and 28S rDNA) and/or mitochondrial (cox 1) genes were provided for both species and the phylogenetic relationships among the ergasilids were tested. Relationships between species/genera are still uncertain in Ergasilidae, but it was possible to verify the formation of 5 well-supported terminal clades – i.e. including a clade formed only by Neotropical species. More molecular data are needed to test this hypothesis, but the clades observed here represent good targets for future taxonomic revisions. The occurrence of R. piranhus specimens in the introduced fish, Co. rendalli can indicate (for the first time) host switching in this parasite species and spillback from native to introduced hosts.